Safe prescribing training provision for junior doctors: is this optimal?. Issue 1 (December 2016) - Kennedy, Maria; Malik, Muzaffar; Haq, Inam; Williams, Sian; Okorie, Michael
Abstract Background The aim of this study was to determine the training provisions in practical safe prescribing for foundation doctors in NHS hospitals located in the South Thames region. Methods A web-based questionnaire was distributed by e-mail to all 1762 foundation doctors in the South Thames Foundation School (STFS) region. In addition, a separate questionnaire was distributed to prescribing training Leads at 15 NHS Hospital Trusts. Quantitative data were analysed using descriptive statistics and thematic analysis was performed on qualitative data. Results Trainers: 10 Prescribing Leads (67 %) responded. Of the 9 NHS Trusts that offered safe prescribing training in their induction programme, 5 included a practical prescribing session. By the end of the foundation year, 6 NHS Trusts had provided at least one dedicated practical prescribing session for F1s compared with 2 NHS Trusts for F2s. Trainees: A total of 124 foundation trainees (7.2 %) responded (69 F1s and 55 F2s). 87 % of F1s received dedicated training in safe prescribing at their Trust induction (n  = 60) in comparison to 49 % of F2s (n  = 27). 80 % of F1s (n  = 55) had a practical prescribing session during induction versus 27 % of F2s (n  = 15). The difference was significant, X 2 (1, N  = 124) = 34.23, p <0.0001. Emerging themes from qualitative data included, recognition of medical education as a continuum, importance of working relationships with pharmacists and neglect of F2s. Conclusions There appears to be a lack of emphasis on the training of F2 doctors in practical safe prescribing compared with F1 doctors. There should be standardisation of safe prescribing training provisions, particularly in the induction period and for F2 doctors.